The representation of 21st-century themes in the English textbooks in the Philippines - Barrot, Jessie Saraza (Universitas Syiah Kuala, 2025)
In an increasingly interconnected and rapidly changing world, the need to equip students with relevant skills and knowledge has become a critical educational priority. English Language Teaching (ELT) textbooks play a crucial role in preparing them for the multifaceted challenges of modern society. However, there is limited research on how effectively these textbooks integrate 21st-century themes. Thus, this study investigates the representation of 21st-century themes in ELT textbooks used in the Philippines. Specifically, this study examines the extent of using 21st-century themes in the ELT coursebooks, the ways these themes are incorporated into the textbooks, and the types of assessment activities where 21st-century themes are incorporated. A descriptive approach was employed to examine 30 textbooks from three major educational publishers. Findings reveal significant variability in the representation of themes such as civic literacy, health literacy, and environmental literacy as well as the three primary methods of integrating these themes. The study highlights a lack of systematic integration of 21st-century themes, largely influenced by the absence of a standardized national curriculum framework and the varied orientations of textbook authors. These results underscore the need for a more comprehensive and balanced integration of 21st-century skills across educational materials. Implications for curriculum development, textbook design, teacher training, and future studies are discussed.